CODE-SWITCHING AS A PEDAGOGICAL TOOL IN ENGLISH LANGUAGE TEACHING - Kdirbayeva Sevara Berdimuratovna (TADQIQOTLAR, 2026)
Annotation:This article examines the pedagogical role of code-switching in English Language Teaching (ELT), particularly in English as a Foreign Language (EFL) classrooms. In multilingual educational environments, teachers and learners frequently alternate between the target language and the native language to facilitate comprehension, classroom interaction, and emotional support. While traditional language teaching approaches often discouraged the use of the first language in English instruction, recent sociolinguistic and pedagogical research increasingly recognizes code-switching as a valuable instructional strategy. Drawing on methodological literature, applied linguistics research, and classroom observations in Uzbek educational contexts, this article analyzes how code-switching supports comprehension, reduces anxiety, increases participation, and enhances communicative competence among EFL learners. The study also discusses the cognitive and sociolinguistic dimensions of code-switching and its role in multilingual classrooms.